A powder-net composite gas diffusion layer and its preparation method and application
By adopting a powder mesh composite gas diffusion layer and combining the sintering technology of the composite titanium mesh layer and the powder titanium film layer, the existing Ti-based gas diffusion layer has been solved in an acidic environment, and the improvement of high support strength, bond strength and electrolytic water efficiency has been achieved.
Patent Information
- Application Number
- CN202211177427.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The existing Ti-based gas diffusion layer is prone to deformity in an acidic environment of high-pressure gas, has low support strength, and the bonding strength between the microporous layer and the diffusion base layer is insufficient, which cannot meet the requirements of high support strength and high bonding strength.
A powder mesh composite gas diffusion layer is adopted, including a composite titanium mesh layer and a powder titanium film layer, and is formed into one through the second sintering to improve the support strength and bond strength, and maintain stable performance in an acidic environment.
It achieves high support strength and high bond strength, can operate stably in an acidic environment of high-pressure gas, and has the characteristics of good breathability, small contact resistance and high electrolytic water efficiency.
Smart Images

Figure CN115478287B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen production by water electrolysis, and specifically relates to a powder-net composite gas diffusion layer and a preparation method and application thereof. Background Art
[0002] Hydrogen production by water electrolysis is to dissociate water molecules into hydrogen and oxygen through an electrochemical process under the action of direct current, and precipitate them at the cathode and anode respectively. According to different electrolytes, it can be mainly divided into three categories: alkaline electrolysis (ALK), proton exchange membrane (PEM) water electrolysis, and solid oxide (SOEC) water electrolysis. The application conditions of SOEC are relatively high, the technology is still in the research stage, and the investment cost is very high. Although the cost of hydrogen production by alkaline water electrolysis is lower, the alkaline electrolyte will bring deeper environmental problems. Compared with the two, PEM water electrolysis hydrogen production can meet the requirements of electrolysis efficiency and cost, and has better chemical stability, proton conductivity, and gas separation. It can effectively prevent electron transfer and improve the safety of the electrolyzer. In addition, PEM water electrolysis can effectively utilize excess photovoltaic and wind power to solve the problem of energy consumption. It is the greenest way to produce hydrogen and is known as the most potential water electrolysis technology.
[0003] The main components of the PEM water electrolyzer are proton exchange membrane, cathode and cathode catalyst layer, cathode and cathode gas diffusion layer, cathode and cathode end plates, etc. The diffusion layer, catalyst layer and proton exchange membrane form the membrane electrode, which is the main place for material transmission and electrochemical reaction in the entire water electrolyzer, and directly affects the performance and life of the PEM water electrolyzer. The current research on reducing the cost of PEM electrolyzers focuses on the core components such as the membrane electrode based on catalyst and PEM, and the gas diffusion layer and bipolar plate. In the PEM water electrolyzer, the gas diffusion layer material has gas permeability and is related to the conductivity and gas production efficiency of the membrane electrode and bipolar plate, and is one of the key materials in the electrolysis of water to produce hydrogen.
[0004] The traditional water electrolysis diffusion layer material is carbon paper. However, since the PEM water electrolysis cell uses a perfluorosulfonic acid membrane, the water electrolysis cell is in a strong acidic environment, and the active oxygen atoms generated by the anode cause carbon oxidation, which causes the catalyst layer to fall off the carbon paper, eventually leading to electrode failure and cannot be used for a long time. Therefore, carbon paper is not suitable for use as an anode gas diffusion layer, and further makes the use of corrosion-resistant and oxidation-resistant Ti-based gas diffusion layers necessary. At present, the Ti-based gas diffusion layer produced domestically mainly uses one or more layers of titanium mesh, titanium grid, etc. as the diffusion layer. A layer of titanium mesh or titanium grid is easy to deform under high-pressure gas environment and has low support strength. Different titanium mesh layers are combined by spot welding or gluing. The bonding strength between the microporous layer and the diffusion base layer is low, resulting in the microporous layer being easy to fall off, and cannot meet the requirements of higher support strength and higher bonding strength. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a powder-mesh composite gas diffusion layer and a preparation method and application thereof. The powder-mesh composite gas diffusion layer has high supporting strength, high bonding strength between the microporous layer and the diffusion base layer, stable performance in acidic environments, and can operate stably in a high-pressure gas acidic environment.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a powder-net composite gas diffusion layer, the powder-net composite gas diffusion layer comprising:
[0008] Composite titanium mesh layer;
[0009] A powder titanium film layer is formed on the composite titanium mesh layer, and the composite titanium mesh layer and the powder titanium film layer are integrated through a second sintering.
[0010] The powder-net composite gas diffusion layer provided by the present invention has high supporting strength, high bonding strength between the microporous layer and the diffusion base layer, stable performance in acidic environments, and can operate stably in a high-pressure gas acidic environment.
[0011] In a second aspect, the present invention provides a method for preparing a powder-mesh composite gas diffusion layer according to the first aspect, comprising the following steps:
[0012] Preparation of powdered titanium film:
[0013] The titanium powder is first sintered and cut to obtain a powder titanium film;
[0014] Preparation of composite titanium mesh:
[0015] Fixing and compounding the multiple layers of titanium mesh together to form a composite titanium mesh;
[0016] Preparation of powder mesh composite gas diffusion layer:
[0017] The powder titanium film and the composite titanium mesh are subjected to a second sintering to form a whole, thereby obtaining a powder mesh composite gas diffusion layer including a composite titanium mesh layer and a powder titanium film layer.
[0018] The preparation method of the powder-net composite gas diffusion layer provided by the present invention is simple to operate. The prepared powder-net composite gas diffusion layer has high supporting strength, high bonding strength between the microporous layer and the diffusion base layer, stable performance in acidic environment, and can operate stably in a high-pressure gas acidic environment.
[0019] In a third aspect, the present invention provides an application of the powder-mesh composite gas diffusion layer as described in the first aspect in at least one of water electrolysis, fuel cells, sensors, and electrochemical reduction of carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic structural diagram of the powder-mesh composite gas diffusion layer provided by the present invention.
[0021] The following are the descriptions of the reference numerals:
[0022] 1. Powder titanium film layer; 2. Composite titanium mesh layer. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the amounts of the experimental reagents, unless otherwise specified, are all the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0025] In a first aspect, an embodiment of the present invention provides a powder-net composite gas diffusion layer, the powder-net composite gas diffusion layer comprising:
[0026] Composite titanium mesh layer;
[0027] A powder titanium film layer is formed on the composite titanium mesh layer, and the composite titanium mesh layer and the powder titanium film layer are integrated through a second sintering.
[0028] Here, the powder titanium film layer is the microporous layer, and the composite titanium mesh layer is the diffusion base layer.
[0029] The powder mesh composite gas diffusion layer provided by the embodiment of the present invention has high supporting strength, high bonding strength between the microporous layer and the diffusion base layer, stable performance in acidic environments, and can operate stably in a high-pressure gas acidic environment; it is thin and has a smooth surface, and has the characteristics of good air permeability, low contact resistance, and high water electrolysis efficiency.
[0030] The powder-mesh composite sintered gas diffusion layer provided by the embodiment of the present invention has both the high air permeability of the titanium mesh layer and the high specific surface area of the powder titanium film layer.
[0031] Furthermore, the titanium mesh in the composite titanium mesh layer is a primary titanium mesh.
[0032] Furthermore, the titanium mesh includes at least one of titanium brushed mesh, titanium square hole mesh, and titanium mat-shaped mesh.
[0033] Furthermore, the powder titanium film in the powder titanium film layer is made of titanium powder through a first sintering, wherein the particle size range of the titanium powder is -100 mesh to +500 mesh (i.e., it can pass through a 100 mesh sieve but not a 500 mesh sieve, i.e., titanium powder with a size of approximately 25 to 150 microns). For example, the particle size range of the titanium powder can be -150 mesh to +250 mesh, -230 mesh to +325 mesh, or -325 mesh to +500 mesh, etc. If the titanium powder particle size is too large, the pore size of the sintered powder titanium film layer will be large, but the pore size of the microporous layer needs to be as small as possible while satisfying the gas permeability effect to improve the contact interface between the diffusion base layer and the catalyst layer. If the titanium powder particle size is too small, the direct contact points between the diffusion base layer and the catalyst layer will increase, thereby promoting the catalytic effect, but the gas permeability effect will be poor, thereby reducing the working efficiency of the gas diffusion layer.
[0034] Further, the second sintering temperature is 900°C to 1400°C, for example, the second sintering temperature is 900°C, 1000°C, 1100°C, 1200°C, 1300°C or 1400°C, etc., preferably 1000°C to 1200°C.
[0035] Furthermore, the thickness of the powder titanium film is 0.2-0.5 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm.
[0036] Furthermore, the composite titanium mesh in the composite titanium mesh layer is made of multiple layers (eg, 3 layers, 4 layers or 5 layers, etc.) of titanium mesh with a thickness of 0.25 mm and / or 0.13 mm, and the thickness of the composite titanium mesh is 0.5-1.5 mm, preferably 0.75 mm.
[0037] Furthermore, the composite titanium mesh in the composite titanium mesh layer is made of multiple layers of titanium mesh with a thickness of 0.25 mm and / or 0.13 mm fixed by spot welding and / or a third sintering.
[0038] In a second aspect, an embodiment of the present invention provides a method for preparing a powder-mesh composite gas diffusion layer according to the first aspect, comprising the following steps:
[0039] S1. Preparation of powder titanium film:
[0040] The titanium powder is first sintered and cut to obtain a powder titanium film;
[0041] S2. Preparation of composite titanium mesh:
[0042] Fixing and compounding the multiple layers of titanium mesh together to form a composite titanium mesh;
[0043] S3. Preparation of powder-mesh composite gas diffusion layer:
[0044] The powder titanium film and the composite titanium mesh are subjected to a second sintering to form a whole, thereby obtaining a powder mesh composite gas diffusion layer including a composite titanium mesh layer and a powder titanium film layer.
[0045] The preparation method of the powder mesh composite gas diffusion layer provided in the embodiment of the present invention is simple to operate, can realize the domestic application of the gas diffusion layer (key material for hydrogen production by electrolysis of water), and promote the rapid layout of national hydrogen energy development; the prepared powder mesh composite gas diffusion layer has a thin thickness, high supporting strength, high bonding strength between the microporous layer and the diffusion base layer, stable performance in an acidic environment, can operate stably in a high-pressure gas acidic environment, and has the characteristics of good air permeability, low contact resistance, and high water electrolysis efficiency.
[0046] The gas diffusion layer prepared in the embodiment of the present invention uses titanium mesh as the diffusion layer base material, which has better flexibility and ductility, ensuring better assembly sealing during use. The microporous layer (powder titanium film layer) prepared by cutting has better thickness consistency and higher surface flatness, and there are no dead corners in the mass transfer process, ensuring the efficiency of the gas diffusion layer.
[0047] The gas diffusion layer prepared in the embodiment of the present invention changes the single structural form of the traditional gas diffusion layer material for hydrogen production by water electrolysis, and solves the problem that carbon paper and carbon cloth are easily corroded under acidic conditions while meeting the requirements of thickness, strength and porosity.
[0048] Furthermore, in step S1: the titanium powder is first sintered in a vacuum or protective gas atmosphere to obtain a titanium block; and the titanium block is multi-wire cut to obtain a powdered titanium film.
[0049] Furthermore, the protective gas is H2 or an inert gas; and the thickness of the titanium block is 40 to 60 mm.
[0050] Furthermore, the multi-wire cutting of the titanium block includes: the cutting wire moves so that the cutting blade material attached to the cutting wire and the surface of the porous titanium block undergo continuous vibration and friction, so as to achieve multi-wire cutting of the porous titanium block, and the workpiece cutting speed (i.e., the worktable downward movement speed) is 7-30 mm / h, for example, the cutting speed can be 7 mm / h, 10 mm / h, 15 mm / h, 20 mm / h, 25 mm / h or 30 mm / h, etc., and the wire speed is 800-1100 m / min For example, the line speed can be 800m / min, 900m / min, 1000m / min or 1100m / min, etc., the wire diameter is 0.08-0.25mm, for example, the wire diameter can be 0.08mm, 0.12mm, 0.14mm, 0.18mm, 0.20mm, 0.22mm or 0.25mm, etc., and the tension is 10-45N, for example, the tension can be 10N, 12N, 15N, 20N, 25N, 30N, 35N, 40N or 45N, etc.
[0051] Further, in step S1: the particle size range of the titanium powder is -100 mesh to +500 mesh, for example, the particle size range of the titanium powder can be -150 mesh to +250 mesh, -230 mesh to +325 mesh, or -325 mesh to +500 mesh, etc.
[0052] Furthermore, the temperature of the first sintering is 1000°C to 1400°C (for example, the temperature may be 1000°C, 1100°C, 1200°C, 1300°C or 1400°C, etc.), preferably 1000°C to 1100°C. If the first sintering temperature is too high, the sintering neck will increase, resulting in densification of the embryo, and a sharp decrease in surface porosity, making it difficult or even impossible for gas to penetrate. If the first sintering temperature is too low, a sintering neck cannot be formed between the powder particles, and there is no bonding strength.
[0053] Furthermore, in step S1, the thickness of the powder titanium film is 0.2 to 0.5 mm. If the powder titanium film is too thick, the overall porosity of the gas diffusion layer will be reduced, the gas permeability will be low, and it will not be able to work normally. If the powder titanium film is too thin, a continuous film layer cannot be formed on the surface of the titanium mesh, the pore distribution is uneven, the contact area with the catalyst layer is small, and the catalytic efficiency is low.
[0054] Furthermore, in step S2: multiple layers of titanium meshes with a thickness of 0.25 mm and / or 0.13 mm are spot welded and / or sintered for the third time and then composited together to form a composite titanium mesh; the thickness of the composite titanium mesh is 0.5-1.5 mm.
[0055] Preferably, the number of layers of the titanium mesh is 3 to 5. If the number of layers is too many, the difficulty of controlling the composite sintering and bonding increases, the porosity decreases after composite, and the gas permeability is low. If the number of layers is too few, composite sintering is relatively easier, but the supporting strength is low.
[0056] The titanium mesh includes at least one of a titanium brushed mesh (the weaving method is twill weaving), a titanium square hole mesh (the weaving method is plain weaving), and a titanium mat-type mesh (the weaving method is dense weaving).
[0057] Furthermore, when the titanium mesh is a titanium square hole mesh, the mesh number of the titanium mesh is at least one of 100, 200, and 500 meshes; when the titanium mesh is a titanium brushed mesh, the specifications of the brushed mesh are pore size (1~4)mm*(0.5~1.5)mm, and wire diameter 0.2~2mm. The specifications of the brushed mesh are usually described by pore size distribution and wire diameter. The pore size distribution is expressed by the long side × short side of the diamond mesh. 0.5~1.5mm is the length range of the short side, and 1~4mm is the length range of the long side. If the wire diameter is too small, composite sintering is relatively easy, but the supporting strength is low; if the wire diameter is relatively thick, the difficulty of composite sintering bonding control increases. Although the supporting strength is high, the toughness of the titanium mesh deteriorates and the sealing performance is poor.
[0058] Further, in step S3: the powder titanium film and the composite titanium mesh are subjected to a second sintering in a vacuum or protective gas atmosphere to form an integral body; the second sintering temperature is 900°C to 1400°C (for example, the temperature may be 900°C, 1000°C, 1100°C, 1200°C, 1300°C or 1400°C, etc.), preferably 1000°C to 1200°C. If the second sintering temperature is too high, the titanium film powder melts, resulting in a dense film layer, and the dense film layer is not formed. The gas cannot pass through. If the temperature is too low, the titanium film layer does not micro-melt, and the composite titanium mesh layers do not micro-melt. The layers are separated, the overall strength is low, and the compressive strength is low. The second sintering temperature is used for insulation, and the insulation time is 2-5h (for example, 2h, 3h, 4h or 5h, etc.). If the insulation time is too long, the manufacturing cost is high. If the insulation time is too short, the sintering bonding strength is low at the same temperature. The protective gas is H2 or an inert gas.
[0059] The embodiment of the present invention uses high-temperature sintering to make the particles on the surface of the titanium film layer micro-melt and bond with the titanium mesh to form a sintering neck, which can act on the entire plane of the titanium mesh layer and has a high bonding strength. In the prior art, different titanium mesh layers are combined by spot welding, which cannot act on the entire plane and can only ensure that the bonding strength is good in the spot-welded areas, but the unspotted areas are in a stratified state.
[0060] In a third aspect, an embodiment of the present invention provides an application of the powder mesh composite gas diffusion layer as described in the first aspect in at least one of water electrolysis, fuel cells, sensors, and electrochemical reduction of carbon dioxide.
[0061] The present invention has been tested for many times, and some test results are cited as references to further describe the invention in detail. The following is a detailed description in conjunction with specific embodiments.
[0062] The structure of the powder mesh composite gas diffusion layer prepared in the following embodiment is as follows: Figure 1 As shown, the powder-mesh composite gas diffusion layer comprises a powder titanium film layer 1 and a composite titanium mesh layer 2 , wherein the powder titanium film layer 1 is formed on the composite titanium mesh layer 2 .
[0063] In the following examples and comparative examples: the surface roughness was measured according to GB / T3505-2000, the air permeability was tested according to ASTM F316-03, the specifications of the titanium wire drawing mesh were pore size (1-4) mm*(0.5-1.5) mm, and the wire diameter was 0.25 mm or 0.13 mm.
[0064] Example 1
[0065] The method for preparing a powder-net composite gas diffusion layer provided in an embodiment of the present invention comprises the following steps:
[0066] S1. Preparation of powder titanium film:
[0067] A square sintering boat is designed according to the shrinkage ratio of titanium powder after loose sintering. Titanium powder with a particle size range of -230 mesh to +325 mesh is loaded into the pre-designed square sintering boat, and sintered at 1050°C for 3 hours in a vacuum furnace. The titanium block is taken out after cooling in the furnace to obtain a titanium block with a thickness of 50 mm. After sintering, the titanium block is placed on the operating table of a multi-wire cutting device. The wire diameter of the multi-wire cutting device is 0.12 mm, and the tension of the cutting wire is 25 N. The cutting speed of the multi-wire cutting device is adjusted to 7 mm / h and the wire speed is 1000 m / min. The multi-wire cutting device is started to make the cutting blade material attached to the cutting wire continuously vibrate and rub against the surface of the porous titanium block. The cutting wire travels along the thickness direction of the titanium block to realize multi-wire cutting of the titanium block to obtain a powder titanium film with a thickness of 0.3 mm, wherein the cutting wire is a diamond wire, and a cutting blade material is attached to the diamond wire, and the cutting blade material is diamond.
[0068] S2. Preparation of composite titanium mesh:
[0069] Prepare three layers of titanium wire drawing mesh, the shape of the holes on the wire drawing mesh is diamond-shaped, the thickness of each layer of titanium mesh is 0.25 mm, each layer is rotated 90°, cross-stacked, and fixed after spot welding to obtain a composite titanium mesh.
[0070] S3. Preparation of powder-mesh composite gas diffusion layer:
[0071] The powder titanium film prepared in step S1 and the composite titanium mesh prepared in step S2 are sintered into one by using a vacuum furnace at a sintering temperature of 1000-1100°C and kept warm for 3 hours, so that the powder particles on the contact surface of the powder titanium film and the composite titanium mesh are in a slightly molten state and are fused with the wire diameter of the composite titanium mesh to form a stable sintering neck. After cooling in the furnace, the powder titanium film is taken out and cut into the required finished product size to obtain a powder mesh composite gas diffusion layer including a composite titanium mesh layer and a powder titanium film layer.
[0072] The prepared powder-mesh composite gas diffusion layer was subjected to a compressive strength test. Under a uniform stress of 3.0 MPa, the surface of the gas diffusion layer did not deform or be damaged, and the microscopic morphology did not change at all. It had high supporting strength and high bonding strength. The powder-mesh composite gas diffusion layer was placed in an acidic environment with a simulated pH value for hydrogen production by electrolysis of water for 100 hours. The permeability of the gas diffusion layer, the microscopic morphology of the powder titanium film layer 1 and the composite titanium mesh layer 2 did not change at all, and the performance in the acidic environment was stable.
[0073] In the prepared powder-net composite gas diffusion layer, the porosity of the powder titanium film layer 1 is 42%, the average pore size of the powder titanium film layer 1 is 13 μm, the overall thickness of the powder-net composite gas diffusion layer is 1 mm ± 0.02 mm, the thickness of the powder titanium film layer 1 is 0.25 mm ± 0.02 mm, and the overall air permeability is 7.2-9.8×10 -4 L / (Pa.min.cm 2 ), good air permeability, meeting the requirements of gas diffusion layer thickness and permeability for hydrogen production by water electrolysis, and effectively improving the efficiency of hydrogen production by water electrolysis.
[0074] In the prepared powder-mesh composite gas diffusion layer, the surface roughness Ra of the powder titanium film layer 1 is 4.525 μm, and the surface and edge of the product are smooth, which can ensure close fit with the proton exchange membrane without puncturing the membrane layer, reduce the contact resistance between the membrane layers, and effectively improve the conductivity.
[0075] The thickness tolerance of the gas diffusion layer prepared in this embodiment is ±0.02 mm.
[0076] Example 2
[0077] The method for preparing a powder-net composite gas diffusion layer provided in an embodiment of the present invention comprises the following steps:
[0078] S1. Preparation of powder titanium film:
[0079] A square sintering boat is designed according to the shrinkage ratio of titanium powder after loose sintering. Titanium powder with a particle size range of -230 mesh to +325 mesh is loaded into the pre-designed square sintering boat, and sintered at 1100°C for 3 hours in an Ar gas atmosphere furnace. The titanium block is taken out after cooling in the furnace to obtain a titanium block with a thickness of 50 mm. After sintering, the titanium block is placed on the operating table of a multi-wire cutting device. The wire diameter of the multi-wire cutting device is 0.12 mm, and the tension of the cutting wire is 25 N. The cutting speed of the multi-wire cutting device is adjusted to 7 mm / h and the wire speed is 1000 m / min. The multi-wire cutting device is started to make the cutting blade material attached to the cutting wire continuously vibrate and rub with the surface of the porous titanium block. The cutting wire travels along the thickness direction of the titanium block to realize multi-wire cutting of the titanium block to obtain a powder titanium film with a thickness of 0.3 mm, wherein the cutting wire is a diamond wire, and a cutting blade material is attached to the diamond wire. The cutting blade material is diamond.
[0080] S2. Preparation of composite titanium mesh:
[0081] Prepare three layers of titanium brushed mesh with diamond-shaped holes. Each layer of titanium mesh is 0.25 mm thick. Each layer is rotated 90° and stacked crosswise. After spot welding, it is sintered into one at 1000°C in an Ar gas atmosphere furnace for 2 hours to obtain a composite titanium mesh.
[0082] S3. Preparation of powder-mesh composite gas diffusion layer:
[0083] The powder titanium film prepared in step S1 and the composite titanium mesh prepared in step S2 are sintered into one by using a vacuum furnace at a sintering temperature of 1000-1100°C and kept warm for 3 hours, so that the powder particles on the contact surface of the powder titanium film and the composite titanium mesh are in a slightly molten state and are fused with the wire diameter of the composite titanium mesh to form a stable sintering neck. After cooling in the furnace, the powder titanium film is taken out and cut into the required finished product size to obtain a powder mesh composite gas diffusion layer including a composite titanium mesh layer and a powder titanium film layer.
[0084] The prepared metal powder mesh composite gas diffusion layer was subjected to a compressive strength test. Under a uniform stress of 3.0 MPa, the surface of the gas diffusion layer did not deform or be damaged, and the microscopic morphology did not change at all. It had high supporting strength and high bonding strength. The metal powder mesh composite gas diffusion layer was placed in an acidic environment with a simulated pH value for hydrogen production by electrolysis of water for 100 hours. The permeability of the gas diffusion layer, the microscopic morphology of the powder titanium film layer 1 and the composite titanium mesh layer 2 did not change at all, and the performance in the acidic environment was stable.
[0085] In the prepared metal powder mesh composite gas diffusion layer, the porosity of the powder titanium film layer 1 is 37%, the average pore size of the powder titanium film layer 1 is 12 μm, the overall thickness of the powder mesh composite gas diffusion layer is 1 mm ± 0.02 mm, of which the thickness of the powder titanium film layer 1 is 0.25 mm ± 0.02 mm, and the overall air permeability is 7.2-9.8×10 -4L / (Pa.min.cm 2 ), good air permeability, meeting the requirements of gas diffusion layer thickness and permeability for hydrogen production by water electrolysis, and effectively improving the efficiency of hydrogen production by water electrolysis.
[0086] In the prepared powder-mesh composite gas diffusion layer, the surface roughness Ra of the powder titanium film layer 1 is 4.799 μm, and the surface and edge of the product are smooth, which can ensure close fit with the proton exchange membrane without puncturing the membrane layer, reduce the contact resistance between the membrane layers, and effectively improve the conductivity.
[0087] Example 3
[0088] The method for preparing a powder-net composite gas diffusion layer provided in an embodiment of the present invention comprises the following steps:
[0089] S1. Preparation of powder titanium film:
[0090] Exactly the same as step S1 in Example 1.
[0091] S2. Preparation of composite titanium mesh:
[0092] Five layers of titanium brushed mesh were prepared, including 4 layers of titanium brushed mesh with a thickness of 0.25 mm and 1 layer of titanium brushed mesh with a thickness of 0.13 mm. The holes on the brushed mesh were in the shape of diamonds. Each layer was rotated 90°, cross-stacked, and fixed after spot welding to obtain a composite titanium mesh.
[0093] S3. Preparation of powder-mesh composite gas diffusion layer:
[0094] Exactly the same as step S3 in Example 1.
[0095] The prepared metal powder mesh composite gas diffusion layer was subjected to a compressive strength test. Under a uniform stress of 3.0 MPa, the surface of the gas diffusion layer did not deform or be damaged, and the microscopic morphology did not change at all. It had high supporting strength and high bonding strength. The powder mesh composite gas diffusion layer was placed in an acidic environment with a simulated pH value for hydrogen production by electrolysis of water for 100 hours. The permeability of the gas diffusion layer, the microscopic morphology of the powder titanium film layer 1 and the composite titanium mesh layer 2 did not change at all, and the performance in the acidic environment was stable.
[0096] In the prepared powder-net composite gas diffusion layer, the porosity of the powder titanium film layer 1 is 45%, the overall thickness of the powder-net composite gas diffusion layer is 1.4 mm ± 0.05 mm, of which the thickness of the powder titanium film layer 1 is 0.25 ± 0.02 mm, and the overall air permeability is 7.2-9.8×10 -4 L / (Pa.min.cm 2 ), good air permeability, meeting the requirements of gas diffusion layer thickness and permeability for hydrogen production by water electrolysis, and effectively improving the efficiency of hydrogen production by water electrolysis.
[0097] In the prepared powder-mesh composite gas diffusion layer, the surface roughness Ra of the powder titanium film layer 1 is 5.076 μm, and the surface and edge of the product are smooth, which can ensure close fit with the proton exchange membrane without puncturing the membrane layer, reduce the contact resistance between the membrane layers, and effectively improve the conductivity.
[0098] Example 4
[0099] The method for preparing a powder-net composite gas diffusion layer provided in an embodiment of the present invention comprises the following steps:
[0100] S1. Preparation of powder titanium film:
[0101] Exactly the same as step S1 in Example 1.
[0102] S2. Preparation of composite titanium mesh:
[0103] Prepare five layers of brushed titanium mesh, including 4 layers of titanium brushed mesh with a thickness of 0.25 mm and 1 layer of titanium brushed mesh with a thickness of 0.13 mm. The holes on the brushed mesh are in the shape of diamonds. Each layer is rotated 90° and stacked crosswise. After spot welding, they are sintered into one at 1000-1100°C in an Ar gas atmosphere furnace for 2 hours to obtain a composite titanium mesh.
[0104] S3. Preparation of powder-mesh composite gas diffusion layer:
[0105] Exactly the same as step S3 in Example 1.
[0106] The prepared powder-mesh composite gas diffusion layer was subjected to a compressive strength test. Under a uniform stress of 3.0 MPa, the surface of the gas diffusion layer did not deform or be damaged, and the microscopic morphology did not change at all. It had high supporting strength and high bonding strength. The powder-mesh composite gas diffusion layer was placed in an acidic environment with a simulated pH value for hydrogen production by electrolysis of water for 100 hours. The permeability of the gas diffusion layer, the microscopic morphology of the powder titanium film layer 1 and the composite titanium mesh layer 2 did not change at all, and the performance in the acidic environment was stable.
[0107] In the prepared powder-net composite gas diffusion layer, the porosity of the powder titanium film layer 1 is 43%, the overall thickness of the powder-net composite gas diffusion layer is 1.4 mm ± 0.05 mm, wherein the thickness of the powder titanium film layer 1 is 0.25 ± 0.02 mm, and the overall air permeability is 7.2-9.8×10 -4 L / (Pa.min.cm 2 ), good air permeability, meeting the requirements of gas diffusion layer thickness and permeability for hydrogen production by water electrolysis, and effectively improving the efficiency of hydrogen production by water electrolysis.
[0108] In the prepared powder-mesh composite gas diffusion layer, the surface roughness Ra of the powder titanium film layer 1 is 4.865 μm, and the surface and edge of the product are smooth, which can ensure close fit with the proton exchange membrane without puncturing the membrane layer, reduce the contact resistance between the membrane layers, and effectively improve the conductivity.
[0109] Comparative Example 1
[0110] The composite titanium mesh prepared in step S2 of Example 1 was used as a gas diffusion layer, and the properties of the composite titanium mesh were tested.
[0111] The prepared composite titanium mesh was subjected to a compressive strength test. When the gas diffusion layer was subjected to a uniform stress of 3.0 MPa, the surface flatness was reduced, the wire diameter showed compression deformation, stratification occurred between the layers of the composite titanium mesh, and there was a tendency for cracking at the spot welding positions. The prepared composite titanium mesh was placed in an acidic environment with a simulated pH value for hydrogen production by electrolysis of water for 100 hours. Under an electron microscope, no corrosion weight gain or wire diameter change was observed on the wire surface, and there was no obvious change in the energy spectrum test composition.
[0112] The prepared composite titanium mesh has a porosity of 65%, an overall thickness of 0.75 ± 0.02 mm, and an overall air permeability of 9 × 10 -4 L / (Pa.min.cm 2 ).
[0113] Comparative Example 2
[0114] The powder titanium membrane layer in the gas diffusion layer in Example 1 was replaced by 6 layers of 500-mesh square-hole woven titanium mesh fixed in layers.
[0115] The average pore size of the microporous layer in the prepared gas diffusion layer is 14 μm, and the porosity is 30%. Compared with Example 1, the gas permeability of the gas diffusion layer is much lower, less than 1×10 -5 L / (Pa.min.cm 2 ), it is difficult to meet the requirements of the microporous layer for porosity and the requirements of the overall gas diffusion layer for permeability.
[0116] Comparative Example 3
[0117] S1. Preparation of composite titanium mesh:
[0118] Exactly the same as step S2 in Example 1.
[0119] S2. Preparation of gas diffusion layer:
[0120] Methyl cellulose is added to titanium powder with a particle size range of -230 mesh to +325 mesh to prepare titanium powder slurry, and a layer of the above slurry with a thickness of 0.3 mm is evenly sprayed on the surface of the composite titanium mesh to form a microporous layer. After natural drying, the titanium powder slurry and the composite titanium mesh prepared in step S1 are placed in a vacuum furnace to sinter them into one. The sintering temperature is 1000-1100°C and the temperature is kept for 3 hours, so that the powder particles on the contact surface of the titanium powder slurry and the composite titanium mesh are in a micro-melted state and fuse with the wire diameter of the composite titanium mesh to form a stable sintering neck. After that, the slurry is taken out after cooling in the furnace and cut into the required finished product size to obtain a gas diffusion layer.
[0121] This comparative example has a carbon-containing binder (methyl cellulose) added during the preparation process. During the sintering process, the carbon-containing material is not completely decomposed and volatilized, and carbon residues exist. As a result, the gas diffusion layer prepared by this comparative example sometimes still corrodes during use under acidic conditions.
[0122] It is difficult to control the uniformity of thickness of the microporous layer prepared by spraying, and the thickness tolerance is usually greater than ±0.02mm. The thickness tolerance of the gas diffusion layer prepared in this comparative example is ±0.05mm, which cannot meet the product's requirements for flatness and will cause difficulties during product assembly.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A powder-net composite gas diffusion layer, characterized in that: The powder-net composite gas diffusion layer comprises: Composite titanium mesh layer; A powder titanium film layer, wherein the powder titanium film layer is formed on the composite titanium mesh layer, and the composite titanium mesh layer and the powder titanium film layer are integrated by a second sintering process; The powder titanium film layer is obtained by first sintering and cutting titanium powder.
2. The powder-mesh composite gas diffusion layer according to claim 1, characterized in that: The powder titanium film in the powder titanium film layer is made of titanium powder through a first sintering process, wherein the particle size of the titanium powder ranges from 100 mesh to 500 mesh.
3. The powder-mesh composite gas diffusion layer according to claim 1, characterized in that: The second sintering temperature is 900°C to 1400°C.
4. The powder mesh composite gas diffusion layer according to claim 2, characterized in that: The thickness of the powder titanium film is 0.2-0.5 mm.
5. The powder mesh composite gas diffusion layer according to claim 1, characterized in that: The composite titanium mesh in the composite titanium mesh layer is made of multiple layers of titanium mesh with a thickness of 0.25 mm and / or 0.13 mm, and the thickness of the composite titanium mesh is 0.5-1.5 mm.
6. A method for preparing a powder-net composite gas diffusion layer according to any one of claims 1 to 5, characterized in that: The steps include: Preparation of powder titanium film: The titanium powder is first sintered and cut to obtain a powder titanium film; Preparation of composite titanium mesh: Fixing and compounding the multiple layers of titanium mesh together to form a composite titanium mesh; Preparation of powder mesh composite gas diffusion layer: The powder titanium film and the composite titanium mesh are subjected to a second sintering to form a whole, thereby obtaining a powder mesh composite gas diffusion layer including a composite titanium mesh layer and a powder titanium film layer.
7. The method for preparing a powder-net composite gas diffusion layer according to claim 6, characterized in that: In the steps of preparing the powder titanium film: the titanium powder is first sintered in a vacuum or protective gas atmosphere to obtain a titanium block; and the titanium block is multi-wire cut to obtain a powder titanium film.
8. The method for preparing a powder-net composite gas diffusion layer according to claim 7, characterized in that: The multi-wire cutting of the titanium block comprises: the cutting wire moves so that the cutting blade material attached to the cutting wire and the surface of the titanium block undergo continuous vibration friction, so as to achieve multi-wire cutting of the titanium block, the workpiece cutting speed is 7-30 mm / h, the wire speed is 800-1100 m / min, the wire diameter is 0.08-0.25 mm, and the tension is 10-45 N; And / or, the first sintering temperature is 1000°C~1400°C.
9. The method for preparing a powder-net composite gas diffusion layer according to claim 6, characterized in that: In the step of preparing the powder-mesh composite gas diffusion layer, the powder titanium film and the composite titanium mesh are subjected to a second sintering in a vacuum or protective gas atmosphere to form a whole; the second sintering temperature is 900°C~1400°C, and the insulation time is 2-5h.
10. Use of the powder-net composite gas diffusion layer according to any one of claims 1 to 5 in at least one of water electrolysis, fuel cells, sensors, and electrochemical reduction of carbon dioxide.
Citation Information
Patent Citations
Application of electric pole gaseous diffusion layer in fuel batter with proton exchange film
CN101140990A
Metal diffusion layer and membrane electrode assembly containing same
CN101638794A